ANALISIS KELAYAKAN POLA USAHATANI AGROTRISULA KOMERING SEJAHTERA V DI DESA BANTAN KECAMATAN BUAY PEMUKA PELIUNG OKU TIMUR - Aisah (Jurnal Bakti Agribisnis, 2016)
The purpose of this research were to: (1) To know the characteristic and technical details, the supporting factor and the constraint of farming pattern of agrotrisula done to farmer group KBS V Desa Bantan, (2) To analyze the profit and feasibility of agrotrisula farming system done to the group Farmer KBS V Desa Bantan. This research was conducted in Bantan Village Buay Pemuka Peliung District, OKU Timur, South Sumatra Province. Location deliberation is done deliberately with the consideration that the Village is one of the pilot Village of agrotrisula farming system in East OKU Regency, when viewed agroclimate the area is very suitable for agrotrisula developed in terms of topography, soil condition and climate. Data collection was carried out until January 2015. This research found that the combination of business that is done is horticulture crops such as long bean, cucumber, sweet corn, ground kangkung, and spinach pull, fishery is cultivation of catfish sangkuriang and farm that is cultivation of bali cattle. Business management is done intensively with commercial purpose, there is special characteristic which is fried by farming group that is application of technology of probiotic bacteria to spur the increase of hormone which can directly increase the growth of both plants, livestock and fish. The total area of cultivated land which KBS V cultivated is 0.32 Ha.Total production costs are sacrificed in one period of agricultural production pattern of agrotrisula pattern of Rp. 22.618.167. The analysis of R / C Ratio is 1.38, which means that every one rupiah sacrificed as business capital will get revenue equal to 1.38 rupiah, and it means feasible to be digested, and ROI (Return On Investment) analysis is obtained value 177% And categorized as very efficient.